(Un)Disciplining Interdisciplinarity: Root Metaphors, Matrices, and the Limits of Psychology in Postmodern Education - Dennis, Jeremy (Journal of Interdisciplinary Studies in Education, 2019)
In interdisciplinary education, metaphors often provide the epistemological clarity that is lacking in our definitions and theories of interdisciplinarity. The problem is that ineffective and unsubstantiated metaphors proliferate. We lack a root metaphor or shared world view of interdisciplinarity. Is it time that we move away from thinking in terms of metaphors? Some instrumentalists in interdisciplinary studies argue yes and propose a pragmatic constructionist approach for interdisciplinary education. This theoretical study determines that this proposal is incomplete. It reveals that an intertextual view of interdisciplinarity is not only more appropriate, but it integrates the competing theoretical and pedagogical approaches in the field. This article also identifies “the matrix” as the metaphor best positioned to sustain this integration and to bridge the widening gap between disciplines.